Provision of Nutritional Drinks for Children in State Elementary School 1 Wangandowo - Auliya Arfiani; Dina Fauziyah Mufidah; Renin Amalia (Experimental Student Experiences, 2024)
As children grow and develop, their nutritional needs are critical to ensure optimal health and development. One important aspect of nutrition is the consumption of healthy and nutritious drinks. Provision of healthy and nutritious drinks in elementary schools can be a means of education about the importance of healthy and nutritious drinks. Through nutrition education programs and activities that involve children, schools can provide knowledge about the benefits of healthy and nutritious drinks for their health. The implementation of community service activities was carried out at SDN 1 Wangandowo, Bojong District, Pekalongan Regency with the target participants being elementary school children in grades 1 and 2 with a total of 31 students. The implementation of this activity uses 2 learning methods, including the lecture method and the discussion method. After holding community service activities in the form of socializing the procurement of nutritious drinks for children in the school environment (SDN 1 Wangandowo), it can be concluded that the provision of nutritious drinks in the elementary school environment is very important and has several basic reasons, including to meet children's nutritional needs, increase concentration and learning performance, encourage healthy eating patterns, prevent health problems, and establish healthy habits early on.